Detection of Dengue Disease Using Artificial Neural Networks - Saha, P; Mandal, R (International Journal of Computer Sciences and Engineering, 2025)
This research paper is aimed at the detection of dengue disease using Artificial Neural Network (ANN). Necessary data was collected from Jalpaiguri Sadar Hospital for training the net. An ANN was designed which detects dengue disease. North Bengal region was aimed for the analysis.